Pengaruh Current Ratio, Return On Asset, Total Asset Turnover, Dan Debt To Total Asset Ratio Terhadap Financial Distress Pada Perusahaan Transportasi Di BEI 2014-2017 - nur laeliyatul mukaromah; Hairul Anam; Satriawaty Migang (MEDIA RISET EKONOMI [MR.EKO], 2022)
This study aims to determine the Influence of Current Ratio, Return On Assets, Total Asset Turnover and Debt to Total Asset Ratio on Financial Distress in transportation companies listed on the Indonesia Stock Exchange (IDX). The data used are financial statements from transportation companies listed on the Indonesia Stock Exchange for the period 2014-2017. The population in this study were 35 companies, and the number of samples used was 11 companies selected using purposive sampling, so obtain 44 observations. Financial distress in this study is measured by Interest Coverage Ratio (ICR). The analytical tool used in this study is Logistic Regression Analysis. The results of the study show that the current ratio, return on assets, debt to total asset ratio variables do not affect financial distress. while the total asset turnover variable affects the financial distress of transportation companies listed on the Indonesia Stock Exchange.